The Relationship Between Adolescent Female Knowledge Levels and Early Marriage Risk - Yanti Srinayanti; Rosmiati Rosmiati; Fairuz Yasmin Salsabila; Asep Gunawan; Elis Roslianti (Genius Midwifery Journal, 2023)
Introductions: Cases of early marriage are now common in various parts of the world. This is of particular concern, considering the many risks that will arise in early marriage or forced marriage, pregnancy at a young age, sexual intercourse at an early age, namely: Sexually transmitted infections, the risk of complications that will occur during pregnancy or childbirth, so can increase maternal and infant mortality. Aims: This study aims to determine the relationship between the knowledge of young women and the risk of early marriage in the working area of the Ciamis Health Center. Methods: The research used a quantitative correlation method with a cross-sectional approach. The population in this study were all pregnant women and mothers who had given birth under the age of 20 in the working area of the UPTD Ciamis Health Center, Ciamis Regency, with as many as 30 respondents. the sample in this study uses Total Sampling. Results: Of the 30 respondents, 1 person had good knowledge (3.3%), 16 people had sufficient knowledge (53.3%) and 13 people had less knowledge (43.3%). out of 30 respondents, 26 people were not at risk of early marriage (86.7%) and as many as 4 were at risk of early marriage (13.3%). Conclusions: Based on the results of statistical tests using the Chi-Square test, a p-value of 0.632 was obtained, when compared to α (0.05), the p-value was more significant than the value of α (0.632 > 0.05), so Ho failed to be rejected, which means that there is no relationship between adolescent knowledge daughter with the risk of early marriage in the Working Area of the UPTD Puskesmas Ciamis.